Tutelaje indígena. Ideas, discuros y prácticas en torno al indio Chiapaneco durante la Primera República - Torres Freyermuth, Amanda Úrsula (2015)
The aim of this article is to understand how thought and acted power groups face the indigenous population, from the study of political culture that prevailed during the First Federal Republic (1824-1835). Understanding the political culture as a set of ideas, values, beliefs and attitudes shared by a certain group. Through state memories, brochures, decrees, constitutions, newspapers, government records, legislative resolutions and books it is shown how, even though the legal status of the Indian changed with Independence, the conditions were created for continue the minority status of Chiapas’ Indian, situation that denied the exercise of political rights acquired with the new government.